2017
DOI: 10.1002/eqe.2978
|View full text |Cite
|
Sign up to set email alerts
|

Is rocking motion predictable?

Abstract: Summary An argument of engineers and researchers against the use of rocking as a seismic response modification technique is that the rocking motion of a structure is chaotic and the existing models are incapable of predicting it well. This argument is supported by the documented inability of rocking models to predict the motion of a specimen excited by a single ground motion. A statistical comparison of the experimental and the numerical responses of a rigid rocking oscillator not to a specific ground motion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 55 publications
1
115
1
3
Order By: Relevance
“…Many studies built on Housner classical model and examined analytically the planar and the 3‐dimensional dynamic behavior of rocking structures (eg, Vassiliou et al and Vassiliou and references therein). Comparisons of analytical with experimental results revealed that predicting the response history of a rocking structure with the aid of the classical model is challenging for a single seismic excitation, yet feasible in an average sense for a suite of records with similar statistical characteristics . Lately, refined numerical and analytical formulations examined flexible structures focusing on the impact, the interaction of rocking with flexural modes, and the influence of deformability on the rocking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies built on Housner classical model and examined analytically the planar and the 3‐dimensional dynamic behavior of rocking structures (eg, Vassiliou et al and Vassiliou and references therein). Comparisons of analytical with experimental results revealed that predicting the response history of a rocking structure with the aid of the classical model is challenging for a single seismic excitation, yet feasible in an average sense for a suite of records with similar statistical characteristics . Lately, refined numerical and analytical formulations examined flexible structures focusing on the impact, the interaction of rocking with flexural modes, and the influence of deformability on the rocking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have built on Housner's classical model, extending their analyses to rocking frames and three‐dimensional rocking structures . Although a precise prediction of the full response history of a rocking oscillator under a given ground motion may be impractical due to the strong nonlinearities involved (eg, negative stiffness) and the uncertainties associated with modelling impact phenomena, Housner's model has been shown capable of predicting the main statistics of the seismic response of rocking structures . In this regard, early studies recognized that rocking motion is highly sensitive to the velocity and acceleration characteristics of the ground motion .…”
Section: Introductionmentioning
confidence: 99%
“…The well‐known coefficient of restitution, ratio of velocity just after impact by velocity right before it, is used to damp oscillations, and it is computed as n the conservation of angular momentum . Several experimental tests show that such analytical previsions usually underestimate energy dissipation . With specific reference to masonry and laboratory campaigns, for fired clay and tuff brickwork, the ratio of experimental to analytical coefficients of restitution was about 95%, and 2 double leaf masonry walls made of approximately dressed stone units with low quality mortar have shown corresponding mean values in the range 95% to 98% .…”
Section: Introductionmentioning
confidence: 99%